Optimalisasi Kesehatan Ibu Hamil melalui Edukasi dan Pendampingan Nyeri Punggung oleh Kader di Karang Intan 2 - Yuliastuti, Erni; Rafidah; Kristiana, Efi (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2025)
Back pain is a common discomfort experienced by approximately 90% of pregnant women due to progressive postural changes caused by uterine enlargement. This condition not only decreases sleep quality but also negatively affects maternal and fetal health, including weakened immunity, increased stress, and higher risks of low birth weight. One effective approach to alleviate back pain during pregnancy is prenatal exercise, which enhances muscle and ligament elasticity, improves posture, and trains breathing as well as relaxation techniques. However, in Sungai Alang Village, all 15 community health cadres lacked knowledge and skills in prenatal exercise. This community service program aimed to improve cadres’ capacity through prenatal exercise training, enabling them to assist pregnant women independently. The methods included pre- and post-tests to assess cadres’ knowledge, practical training on safe exercise techniques, development of illustrated leaflets, and video tutorials for sustainable learning. Monitoring and evaluation were conducted to measure cadres’ progress in knowledge and practice. The results indicated increased understanding among cadres regarding prenatal exercise, improved ability to support pregnant women during maternal classes, and the availability of educational media such as leaflets and videos. Additional outcomes included publications in newspapers, video documentation uploaded to the Poltekkes Kemenkes Banjarmasin YouTube channel, and submission to a nationally accredited journal. In conclusion, empowering community health cadres is an effective strategy to assist pregnant women in managing back pain through prenatal exercise while strengthening community-based maternal health support systems.